Late histological findings in symptomatic COVID-19 patients: A case report. Issue 28 (10th July 2020) - Aiolfi, Alberto; Bruni, Barbara; Biraghi, Tullio; Montisci, Andrea; Miceli, Antonio; Baronio, Barbara; Khor, Desmond; Cirri, Silvia; Donatelli, Francesco; Clemente, Claudio; Bona, Davide
Abstract: Rationale: Although there have been several studies describing clinical and radiographic features about the novel coronavirus (COVID-19) infection, there is a lack of pathologic data conducted on biopsies or autopsies. Patient concerns: A 56-year-old and a 70-year-old men with fever, cough, and respiratory fatigue were admitted to the intensive care unit and intubated for respiratory distress. Diagnosis: The nasopharyngeal swab was positive for COVID-19 and the chest Computed Tomography (CT) scan showed the presence of peripheral and bilateral ground-glass opacities. Interventions: Both patients developed pneumothoraces after intubation and was managed with chest tube. Due to persistent air leak, thoracoscopies with blebs resection and pleurectomies were performed on 23rd and 16th days from symptoms onset. Outcomes: The procedures were successful with no evidence of postoperative air-leak, with respiratory improvement. Pathological specimens were analyzed with evidence of diffuse alveolar septum disruption, interstitium thickness, and infiltration of inflammatory cells with diffuse endothelial dysfunction and hemorrhagic thrombosis. Lessons: Despite well-known pulmonary damages induced by the COVID-19, the late-phase histological changes include diffused peripheral vessels endothelial hyperplasia, in toto muscular wall thickening, and intravascular hemorrhagic thrombosis.